2007
DOI: 10.1134/s0006297907010075
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between Fusarium strains investigated by FT-IR spectroscopy

Abstract: The structural characteristics of Fusarium have received attention from both pure and applied scientists. Because many genes and physiological mechanisms are involved in the development of a particular structure type, this research is complicated. For revealing the structure of macromolecule in these fungal cells, FT-IR spectroscopy combined with multivariate statistical analysis was performed to characterize the structure of protein and polysaccharide of spores and mycelia obtained from different culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The FTIR absorption spectra of F. graminearum local isolates investigated in this study, showed an overall spectral feature similar to those previously reported for this species (Fig. 2) (Nie et al, 2007a;Salman et al, 2012). Spectra were dominated by a large absorption band at 1200-900 cm −1 , the so-called window 4 (W 4 ), mainly attributed to carbohydrate vibrations (Naumann, 2000).…”
Section: Phenotypic Diversity Of F Graminearum Local Isolatessupporting
confidence: 85%
See 1 more Smart Citation
“…The FTIR absorption spectra of F. graminearum local isolates investigated in this study, showed an overall spectral feature similar to those previously reported for this species (Fig. 2) (Nie et al, 2007a;Salman et al, 2012). Spectra were dominated by a large absorption band at 1200-900 cm −1 , the so-called window 4 (W 4 ), mainly attributed to carbohydrate vibrations (Naumann, 2000).…”
Section: Phenotypic Diversity Of F Graminearum Local Isolatessupporting
confidence: 85%
“…The chitin band, which is specific to fungi, was detected at 1151 cm − 1 and 1076 cm − 1 due to its C\ \O and C\ \C stretching vibrations (Nie et al, 2007a;Salman et al, 2012), and the glycogen C\ \O stretching vibrations were detected at the band 1028 cm −1 (Naumann, 2000). The infrared spectra associated with the fungal protein absorptions exhibited the typical amide I and amide II bands at 1640 cm −1 and 1546 cm −1 , respectively, with relatively low intensity as previously observed for Fusarium genus by Nie et al (2007a) and Salman et al (2011). The main spectral features in the high wavenumber region W 1 (between 2800 and 3000 cm − 1 ), were the bands detected at 2922 and 2853 cm −1 , assigned to the anti- Fig.…”
Section: Phenotypic Diversity Of F Graminearum Local Isolatesmentioning
confidence: 99%
“…The amide I and II bands (1700–1485 cm −1 ), which likely arise from fungal proteins, were prominent. The fingerprint region of FHB hyphae was dominated by a broad peak near 1035 cm −1 [ 44 , 63 ]. Accordingly, the broad and strong absorption of this peak in the floret of infected cultivars in combination with a visible alteration in the protein region (α-helix turned to β-sheet) following pathogenic infection, maybe used as a signature marker for pathogenic infection with FHB.…”
Section: Discussionmentioning
confidence: 99%
“…[34] According to previous literatures, the band of 1700-1000 cm −1 is the dominating region which is attributed by organic material in macrofungi. [34,35] Among them, the peak around 1650 cm −1 is mainly caused by protein amide II and the band around 1550 cm −1 belongs to protein amide II absorption. [36,37] Hence, this region of 1720-1480 cm −1 is highly relevant to protein substances.…”
Section: Analysis Of Original Spectramentioning
confidence: 99%